A voyage planning tool for ships sailing between Europe and Asia via the Arctic - Li, Zhiyuan; Ringsberg, Jonas; Rita, Francisco (Ships and Offshore Structures, 2021)
The Arctic is rapidly transforming into a navigable ocean because of global warming reducing the extent of sea ice. As a consequence, a large percentage of the sailing distance between Europe and Asia could be saved by alternatively sailing through the Arctic rather than the traditional route via the Suez Canal. However, taking Arctic routes is fraught with risks and additional costs due to sea ice. The major purpose of this study is to develop a voyage planning tool to improve the safety and fuel efficiency of commercial ships sailing between Europe and Asia via the Arctic, which is achieved by voyage optimization through frequently updated meteorological, oceanographic and ice forecasting. This tool is characterized by route planning for the entire voyage, inclusive of the Arctic passage and the open water legs in Asia and Europe. A single-objective optimization for minimizing fuel consumption under various environmental and operational conditions is established. The resistance model accounts for both ice thickness and ice concentration of unconsolidated Arctic sea ice in the summer. Ice related risks defined in the Polar Operational Limit Assessment Risk Indexing System (POLARIS) are dealt as constraint. Other constraints such as avoidance of land and shallow water are also included. These functions are demonstrated by the two case study vessels sailing between Rotterdam and Shanghai via both the Arctic and the traditional routes.